1997
DOI: 10.1103/physrevd.55.7165
|View full text |Cite
|
Sign up to set email alerts
|

Effective vector-boson approximation applied to hadron-hadron collisions

Abstract: An improved effective vector-boson approximation is applied to hadron-hadron collisions. The effective vector-boson approximation in this form is accurate enough to reproduce the result of a complete perturbative calculation for the specific example of ZZ production within 10%. This is true even far away from a possible Higgs boson resonance and thus in a region where the transverse intermediate vector bosons give the dominant contribution. Simple approximate formulas which greatly reduce the calculational eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(146 reference statements)
0
14
0
Order By: Relevance
“…PYTHIA is a parton shower code which uses the Effective Vector Boson Approximation (EVBA) [7,8] to compute the cross section for VV scattering processes. The choice of the MC generator to be used for the simulation is therefore a key aspect for this study.…”
Section: Generators For Six Fermion Final States and Vv -Fusion Prmentioning
confidence: 99%
“…PYTHIA is a parton shower code which uses the Effective Vector Boson Approximation (EVBA) [7,8] to compute the cross section for VV scattering processes. The choice of the MC generator to be used for the simulation is therefore a key aspect for this study.…”
Section: Generators For Six Fermion Final States and Vv -Fusion Prmentioning
confidence: 99%
“…The corresponding expressions for a pseudorapidity cut are obtained by replacing z min (y), z max (y) and y max in [33] by the expressions (2). We use the exact vector boson pair luminosities of [33] if V 1 V 2 consists of two massive vector bosons. If a photon is involved, the Approximation 2 of [33] with the photon distribution function of [48] is used.…”
Section: Vector Boson Fusionmentioning
confidence: 99%
“…We calculate the invariant mass distribution of the cross-section for h 1 h 2 → V 1 V 2 → V 3 V 4 in the improved EVBA according to [33]. The formulas which have been given there apply if a rapidity cut is used.…”
Section: Vector Boson Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the Drell-Yan contribution and the one of vector boson scattering were of comparable magnitude. However, as in [5], the vector boson scattering processes were calculated using the EVBA for all intermediate boson helicities.Recently [32,33] we showed that an improved version of the EVBA can increase the reliability of EVBA calculations. In particular, the improved EVBA could well reproduce the result of a complete perturbative calculation for a process which is dominated by the transverse intermediate helicities.In this article we carry out a comparison of Drell-Yan production and vector boson scattering using the improved EVBA and including the influence of anomalous couplings.…”
mentioning
confidence: 99%